Safety attitudes, burnout and well-being among healthcare workers during the COVID-19 pandemic: an Indo-Pacific regional cross-sectional study - Abhiram Kanneganti; Benjamin Yong Qiang Tan; Nik Hisamuddin Nik Ab Rahman; Aloysius Sheng-Ting Leow; Max Denning; Ee Teng Goh; Lucas Jun Hao Lim; Ching-Hui Sia; Ying Xian Chua; James Kinross; Melanie Tan; Li Feng Tan; et al. (Singapore Medical Journal)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has had an unprecedented impact in Asia and has placed significant burden on already stretched healthcare systems. We examined the impact of COVID-19 on the safety attitudes among healthcare workers (HCWs), as well as their associated demographic and occupational factors, and measures of burnout, depression and anxiety. Methods: A cross-sectional survey study utilising snowball sampling was performed involving doctors, nurses and allied health professions from 23 hospitals in Singapore, Malaysia, India and Indonesia between 29 May 2020 and 13 July 2020. This survey collated demographic data and workplace conditions and included three validated questionnaires: the Safety Attitudes Questionnaire (SAQ), Oldenburg Burnout Inventory and Hospital Anxiety and Depression Scale. We performed multivariate mixed-model regression to assess independent associations with the SAQ total percentage agree rate (PAR). Results: We obtained 3,163 responses. The SAQ total PARs were found to be 35.7%, 15.0%, 51.0% and 3.3% among the respondents from Singapore, Malaysia, India and Indonesia, respectively. Burnout scores were highest among respondents from Indonesia and lowest among respondents from India (70.9%–85.4% vs. 56.3%–63.6%, respectively). Multivariate analyses revealed that meeting burnout and depression thresholds and shifts lasting ≥12 h were significantly associated with lower SAQ total PAR. Conclusion: Addressing the factors contributing to high burnout and depression and placing strict limits on work hours per shift may contribute significantly towards improving safety culture among HCWs and should remain priorities during the pandemic.